Integrated Multiomic Analysis Reveals the High-Fat Diet Induced Activation of the MAPK Signaling and Inflammation Associated Metabolic Cascades via Histone Modification in Adipose Tissues - Wang, Zhe; Zhu, Ming; Wang, Meng; Gao, Yihui; Zhang, Cong; Liu, Shangyun; Qu, Shen; Liu, Zhongmin; Zhang, Chao (Frontiers in Genetics, 2021)
Background: The number of diet induced obese population is increasing every year, and the incidence of type 2 diabetes is also on the rise. Histone methylation and acetylation have been shown to be associated with lipogenesis and obesity by manipulating gene expression via the formation of repression or activation domains on chromosomes. Objective: In this study, we aimed to explore gene activation or repression and related biological processes by histone modification across the whole genome on a high-fat diet (HFD) condition. We also aimed to elucidate the correlation of these genes that modulated by histone modification with energy metabolism and inflammation under both short-term and long-term high-fat diet conditions. Method: We performed ChIP-seq analysis of H3K9me2 and H3K9me3 in brown and white adipose tissues (subcutaneous adipose tissue) from mice fed with a standard chow (SCD) or HFD and a composite analysis of the histone modification of H3K9me2, H3K9me3, H3K4me1 and H3K27ac throughout the whole genome. We also employed and integrated two bulk RNA-seq and a single-nuclei RNA sequencing dataset and performed western blotting (WB) to confirm the gene expression levels in adipose tissue of the SCD and HFD groups. Results: The ChIP-seq and transcriptome analysis of mouse adipose tissues demonstrated that a series of genes were activated by the histone modification of H3K9me2, H3K9me3, H3K4me1 and H3K27ac in response to HFD condition. These genes were enriched in KEGG pathways involved in lipogenesis, energy metabolism and inflammation. Several genes in the activated MAPK pathway might be related to both inflammation and energy metabolism in mice, rats and humans fed with HFD for a short or long term, as showed by bulk RNA-seq and single nuclei RNA-seq datasets. Western blot analyses further confirmed the increased expression of MET, VEGFA and the enhanced phosphorylation ratio of p44/42 MAPK upon HFD treatment. Conclusion: This study expanded our understanding of the influence of eating behavior on obesity and could assist the identification of putative therapeutic targets for the prevention and treatment of metabolic disorders in the future.